MAPPING OF LONG LINE FISHING GROUND IN THE FISHING PORT OF THE OCEAN (PPS) BUNGUS DISTRICTS TELUK KABUNG PADANG PROVINCE WEST SUMATERA - Muhammad Irvan; Alit Hindri Yani; Usman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The purpose of this study is to determine the area tishi tor long line with a heat map setting in western Sumatra in 2015. The method used in this study is a survey method. The results of this study indicate the location of long line fishing ground is in the zone of archipelagic waters, depths, territorial sea, contiguous zone, ZEE and the high seas. seen from the results of catching the most is the transitional season II in the amount of 47. 232 kg while the catch at least the first transitional season that is equal to 17. 783 kg. significant correlation level with the coordinates of the catch and the more extensive range area of the arrest, the greater the results obtained fishermen. Poot arrest hos point fewest arrests West season with one point while most is the transition season 2 is two points hotspots with a radius of 0.2.Keywords: heatmap setting, Long Line, hotspots, point coordinates, fishing ground